Investigating Media Discourse on the Narrative Construction of Violence and Sexual Harassment in Islamic Boarding Schools - Sekar Putri; Yera Yulista (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study examines how mainstream Indonesian media Detik.com and CNNIndonesia.com, construct narratives surrounding violence and sexual harassment in Islamic boarding schools (pondok pesantren), as well as the resulting public opinion in Bangka Belitung and institutional reputation management efforts. Using Teun A. Van Dijk’s Critical Discourse Analysis, the research analyzes news texts at the macro, superstructure, and micro levels, along with journalist cognition and social context. Primary data were obtained through in-depth interviews with parents, community members, and pesantren leaders, while secondary data consisted of 2022 news articles. The findings reveal competing media narratives: Detik.com employed a more aggressive framing by explicitly naming religious figures and institutions, reinforcing narratives of power abuse, whereas CNNIndonesia.com emphasized physical violence and law enforcement responses. These media framings generated public anxiety and a crisis of trust, compelling pesantren institutions to adopt proactive reputation management strategies. The study confirms the significant influence of media framing on public perception and emotional response